Culture Clash: The Costs and Benefits of Homogeneity - Van den Steen, Eric (Management Science, 2010)
This paper develops an economic theory of the costs and benefits of corporate culture—in the sense of shared beliefs and values—in order to study the effects of “culture clash” in mergers and acquisitions. I first use a simple analytical framework to show that shared beliefs lead to more delegation, less monitoring, higher utility (or satisfaction), higher execution effort (or motivation), faster coordination, less influence activities, and more communication, but also to less experimentation and less information collection. When two firms that are each internally homogeneous but different from each other merge, the above results translate to specific predictions about how the change in homogeneity will affect firm behavior. This paper's predictions can also serve more in general as a test for the theory of culture as shared beliefs.